2017
DOI: 10.1371/journal.pone.0172463
|View full text |Cite
|
Sign up to set email alerts
|

Increased liver-specific proteins in circulating extracellular vesicles as potential biomarkers for drug- and alcohol-induced liver injury

Abstract: Drug- and alcohol-induced liver injury are a leading cause of liver failure and transplantation. Emerging evidence suggests that extracellular vesicles (EVs) are a source of biomarkers because they contain unique proteins reflecting the identity and tissue-specific origin of the EV proteins. This study aimed to determine whether potentially hepatotoxic agents, such as acetaminophen (APAP) and binge alcohol, can increase the amounts of circulating EVs and evaluate liver-specific EV proteins as potential biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 55 publications
4
89
0
Order By: Relevance
“…EVs were isolated from the plasma of patients with alcoholism and control individuals in order to evaluate the increased secretion of P450 proteins, including CYP2E1, in EVs by alcohol exposure . Compared to the age‐matched controls (n = 9, 17.2 ± 3.3), serum aspartate aminotransferase levels in patients with alcoholism (n = 14, 69.9 ± 33.4) were significantly increased, indicating alcohol‐induced liver damage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EVs were isolated from the plasma of patients with alcoholism and control individuals in order to evaluate the increased secretion of P450 proteins, including CYP2E1, in EVs by alcohol exposure . Compared to the age‐matched controls (n = 9, 17.2 ± 3.3), serum aspartate aminotransferase levels in patients with alcoholism (n = 14, 69.9 ± 33.4) were significantly increased, indicating alcohol‐induced liver damage.…”
Section: Resultsmentioning
confidence: 99%
“…The inset figures represent transmission electron microscopy images. (B) EV size was determined by a Nanoparticle Tracking analysis (Nanosight) . (C) Total number of EVs in the sera of healthy controls or patients with alcoholism was measured by Nanosight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that a single dose of ethanol at 6 g/kg administered by gavage successfully [17] causes liver histopathologies, such as microvesicular steatosis and necrosis in hepatocytes, which are characterized by cell enlargement and nuclear dissolution [19]. In the present study, the same ethanol dose (6 g/kg) was administered to the mice once a day for three days.…”
Section: Histological Examination Of Liver Tissuementioning
confidence: 67%
“…Mice in the ethanol-treated groups were exposed to an acute dose of 6 g ethanol/kg body weight administered by gavage once a day for three days (0, 24, and 48 h), whereas control mice received an equal volume of water by oral administration. [17] All animals were sacrificed at 12 h after the third ethanol administration (Table 1).…”
Section: Experimental Protocolmentioning
confidence: 99%